The CpG-sites of the CBX3 ubiquitous chromatin opening element are critical structural determinants for the anti-silencing function - Jessica Kunkiel (Nature Portfolio, 2017)
Abstract Suppression of therapeutic transgene expression from retroviral gene therapy vectors by epigenetic defence mechanisms represents a problem that is particularly encountered in pluripotent stem cells (PSCs) and their differentiated progeny. Transgene expression in these cells, however, can be stabilised by CpG-rich ubiquitous chromatin opening elements (UCOEs). In this context we recently demonstrated profound anti-silencing properties for the small (679 bp) CBX3-UCO element and we now confirmed this observation in the context of the defined murine chromosomal loci ROSA26 and TIGRE. Moreover, since the structural basis for the anti-silencing activity of UCOEs has remained poorly defined, we interrogated various CBX3 subfragments in the context of lentiviral vectors and murine PSCs. We demonstrated marked though distinct anti-silencing activity in the pluripotent state and during PSC-differentiation for several of the CBX3 subfragments. This activity was significantly correlated with CpG content as well as endogenous transcriptional activity. Interestingly, also a scrambled CBX3 version with preserved CpG-sites retained the anti-silencing activity despite the lack of endogenous promoter activity. Our data therefore highlight the importance of CpG-sites and transcriptional activity for UCOE functionality and suggest contributions from different mechanisms to the overall anti-silencing function of the CBX3 element.